PERLINDUNGAN HUKUM PENCIPTA TERHADAP PLAGIASI DI APLIKASI WATTPAD BERDASARKAN UU HAK CIPTA - Aqilah Shafa Qhintara Idris; Rakhmita Desmayanti (Fakultas Hukum Universitas Trisakti, 2022)
In this digital era, digital literacy is a form of work that is well known to many people, moreover, there are many platforms that are ready to accommodate digital literature writers, one of which is Wattpad, but due to the openness of any information on the internet, any work can be accessed by easy and free, that's why many people misuse it with plagiarism. The formulation of the problem is how is legal protection for creators of literary works whose works are plagiarized on the Wattpad application and what sanctions can be imposed on individuals who plagiarize on the Wattpad application. The type of research used is normative, the nature of the research is descriptive, the data sources use primary and secondary data, qualitative data analysis, and the method of drawing conclusions uses deductive logic. Based on the results of the analysis, it is concluded that legal protection for creators of literary works whose works are plagiarized has been provided internationally as well as in national legal instruments. In national legal instruments, the exclusive rights of creators of literary works are protected under Law no. 28 of 2014 concerning Copyright. Other parties who violate CW novels by plagiarizing can be given sanctions, namely in the form of civil sanctions and criminal sanctions.